The Attitude of the Theologians Towards Aristotelean Principles (Damascus University Journal of arts and humanities sciences, 2021)
This paper aims to reveal the attitude and criticism of the scholars of the Aristotelean rules, and to discuss whether this criticism is a natural result of their studying to understand God, or just a primary cognitional attitude towards these rules.The study attempts to reveal the history of the logical and ontological criticism of these concepts in the context of the history of philosophy and the Greek logic, and seeks to examine whether this Greek criticism have had a direct or indirect influence on the Islamic scholars in their criticism of these rules. The research focuses on examining the attitude of the speaker whether it is a criticism to this criticism, trying to scan the whole speaking schools to reveal the effect of their attitudes towards this criticism.The study addresses the two critical trends of Mu'tazil and Ash'ariyah shedding light on the endeavors of abo Hashem Aljabaee, Alghazali, Al Mu'tazil, and Fakhr Aldeen Alrazi, the Ash’ariyah in criticizing these rules. Finally, the present study introduces the endeavors of modern logic to analyze and criticize Aristotelean logic rules –on a scientific not a theologian bases.
Keywords: The Attitude of the Theologians Towards Aristotelean Principles